Clinical Response of Human Pulp Tissue to Direct Pulp Capping with Mineral Trioxide Aggregate and Propolis - Beg, Zainab; Sheikh, Abubakr; Islam, Shahid; Aliuddin, Azam Muhammad; Khan, Abdullah (Indus Journal of Bioscience Research, 2025)
Objective: To compare the clinical outcomes of mineral trioxide aggregate (MTA) and propolis when used as a direct pulp capping material in permanent teeth in which carries removal incurred in the exposure of the pulp. Methods: This quasi-experimental, single blind study included a total of 110 patients, aged between 18 and 45. Patients with deep carious lesions and signs and symptoms of reversible pulpitis were included. Teeth that developed pulp exposure during caries excavation were selected for the study. Once hemostasis was achieved, the direct pulp capping agent used was either mineral trioxide aggregate (MTA) or propolis, and the definitive restoration was performed with resin composite. After four months, patients were recalled for clinical and radiographic evaluation. The absence of spontaneous pain, no tenderness to percussion, a positive response to pulp vitality testing, and no radiographic evidence of periapical pathology were considered criteria for clinical success. The Chi-square test and Fisher's Exact test were employed for statistical analysis. Results: Clinical success was observed in 80.0% of the MTA group (44/55) and 72.7% of the propolis group (40/55) at four months. Despite the fact that MTA exhibited a higher success rate, the difference between the two groups was not statistically significant (p = 0.501). The majority of the teeth that were treated were posterior, and no significant correlation was observed between the type of tooth and the outcome of the treatment. Conclusion: As direct pulp capping agents in cariously exposed permanent teeth, both MTA and propolis showed good short-term results. Although MTA remains the preferred material, propolis with its natural source, biological action, and less cost may be a good substitute. More long-term, clinical studies are required to prove its clinical consistency and effectiveness.